Fecundação in Vitro de Ovócitos Bovinos com Sêmen Submetido a Diferentes Diluidores - Coelho, Lia De Alencar; Esper, César Roberto [UNESP]; Garcia, Joaquim Mansano [UNESP]; Vantini, Roberta [UNESP]; Almeida Jr., Ivo Luis [UNESP] (My University, 2000)
This study investigated the effect of semen extender on in vitro development of bovine oocytes after in vitro maturation and fertilization. The ejaculate from one bull was divided in three parts which were diluted with three different extenders: Egg yolk/Lactose (EYL), Egg yolk/Citrate (EYC) and Egg yolk/Tris (EYT). Samples of semen diluted with these extenders were frozen in liquid nitrogen and, after thawing, were filtered by discontinuous Percoll gradient. The sperm concentration was adjusted to 10× 106 cells/mL and the sperm capacitation was induced with 10 μg/mL of heparin. After 24 hours of culture for in vitro maturation, the oocytes, aspirated from ovarian follicles, were inseminated with semen diluted in TALP medium and 48 h after the zigotes were transferred into droplets prepared with TCM-199 medium containing 5% of bovine fetal serum, 5% of estrous cow serum and bovine oviduct epithelial cells in suspension under silicon oil and were further cultured of 9 days. All the cultures were performed at 38.5°C in 5% CO 2 in air. Data were analyzed by chi-square analysis. There was a significant difference in terms of cleavage rate (CR) with means of 66.0, 69.3 and 54.4% for EYL, EYC and EYT, respectively. There were no differences in terms of the morulae/blastocysts and hatching rates. These results suggest that the semen extender had no effect on in vitro development of bovine, even the CR have been affected.
In Vitro Fertilization of Bovine Oocytes with Semen Submitted to Different Extenders
Keywords: Bovine; Cleavage rate; Embryo; In vitro fertilization; Semen extender